Association of liver function test parameters with hematological indices in seropositive Hepatitis B patients - Timalsina, Santosh; Nepal, Sandesh; Mahato, Shishir (Journal of Chitwan Medical College, 2020)
Background: Inflammation is increasingly being implicated for progression of Chronic Hepatitis B. Besides the usual liver function test (LFT) parameters, systemic inflammatory markers such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have generated significant interest that could be useful in stratifying the severity and prognosis of liver disease. The aim of this study was to compare LFT parameters and hematological ratios (NLR and PLR) between seropositive hepatitis B patients and healthy controls and explore associations between them. Methods: This cross-sectional study included 64 Hepatitis B surface antigen (HBsAg) positive patients and 62 apparently healthy seronegative individuals visiting Chitwan Medical College between March to October 2019. Laboratory data included standard LFT panel and hematological parameters including NLR and PLR. Data was analyzed using SPSS software, version 20. P<0.05 was considered to be statistically significant. Results: The two groups (seropositive and seronegative group) did not differ by age and gender. LFT parameters except for total protein were higher in the seropositive group. Both median NLR and PLR were considerably lower in the seropositive group compared to the seronegative group (2.99 and 102.32 vs. 3.67 and 126.15 respectively). However, NLR showed a considerable overlap between the groups, indicating a high variability. No significant correlation was observed between these hematological indices with other LFT parameters. Conclusions: NLR and PLR are easily obtainable, cost-effective parameters that are inversely related with Hepatitis B infection. They could supplement routine LFT parameters in characterization of the phase and severity of chronic Hepatitis B infection.